Attainment of the Number Concept by Children aged between 4–7 - RAMAZAN, MÜSLİMAT OYA (SAGE Publications Ltd, 2010)
The main purpose of this research is to determine whether the attainment of the number concept by children aged between 4–7 differs depending on age variant as well as receiving preschool education or not. Attainment of the number concept has been examined by means of One-to-One Matching Test consisting of Piaget's experiments. The test was applied to 268 students receiving education in private and public schools in Istanbul. The sampling group was classified into children aged 4, 5, 6, and 7. As a result, it was observed that achievement in One-to-One Matching Test increases according to age, but no significant difference was determined between the ages of 5 and 6. © 2010 A B Academic Publishers Printed in Great Britain.